Global economic cooperation views from G20 countries - Kathuria, Rajat; Nagpal, Neetika Kaushal (Springer, 2016)
This book discusses issues such as global financial crisis and global governance, food security, energy sustainability, the global financial system, trade and protectionism, and growth and employment. Since the outbreak of the financial as well as national debt crises in the Euro zone, the focus of the G20 has shifted back to addressing short-term issues. These issues range from the dynamic effects of global imbalances and the appropriate degree of financial sector regulation to questions of austerity versus growth and the lack of a comprehensive framework for managing the international monetary system. A further issue is the relevance of the G20 agenda for emerging market economies. Global economic recovery still remains fragile and downside risks to global growth remain. Additionally, much of the agenda of the Seoul Development Consensus for shared growth launched in 2010 has yet to be fulfilled. A key discussion point in the book, therefore, is how to make a tangible and significant difference in people's lives by implementing an agenda of inclusive growth.